The Use of e-Learning Course during the COVID-19: A Systems Thinking Approach - Liu, Chin-Yen Alice (International Journal of Management Excellence (ISSN: 2292-1648), 2020)
In the era of theInternet, most educators have been supported by powerful tools ranging from e-books and e-learning sites to cloud services, and students’ learning environment has been a mix between traditional study (in class) and e-learning through some kind of online learning platform. Due to the uncertainty of the rapidly changing COVID-19 situation, all colleges and universities have to shutter their physical campuses and move their courses to remote and online formats hastily. This prompted many to wonder if all of the faculty are ready and qualified to teach online courses and/or if all of the students are ready to learn in the comprehensive online environment. If not, what ultimate impact will be to our higher education during this national emergency virus pandemic since there is no choice but depend on where they sit currently, not to mention the negative reviews and concerns regarding the online education. To make this transfer seamlessly and conflict mitigation, this paper applied systems thinking for an e-Learning course and proposed a flexible grading method for an e-learning environment, which will enhance students’ grades by allowing students to control their own study paces and the amount of efforts spent in the course, which can bring a successful online learning experience.